The Smart Enough City: Putting Technology in Its Place to Reclaim Our Urban Future - Green (MIT Press, 2019)
Monograph
fulltext
Keywords: Computing and Processing; Communication, Networking and Broadcast Technologies; Components, Circuits, Devices and Systems; General Topics for Engineers